Navigating technological advancements in two faces of institutions for sustainable development goals: Insights from the transportation sector in rapidly urbanizing developing economies - Vu Thi Kim Hanh; Nguyen Hong Nga (Sustainable Futures)
This study investigates how institutional factors influence the application of technological advancements and the sustainable transportation goal in alignment with the Sustainable Development Goals (SDGs) within small and medium-sized enterprises in the transportation sector (transportation SMEs). Grounded in institutional theory and dynamic capabilities theory, the study positions the application of technological advancements as being enabled through sensing, seizing, and transforming capabilities under resource constraints and complex regulations. Data were collected from 350 transportation SMEs in Ho Chi Minh City, Vietnam, using stratified probability sampling and analysed through partial least squares structural equation modelling. The results show that negative institutional factor, including legal uncertainty, data security concerns, and cultural resistance, directly and negatively impacts the application of technological advancements through seizing and transforming capabilities. Conversely, positive institutional factor, such as supportive legal frameworks and government incentives, directly and positively impacts the application of technological advancements through these two capabilities and the SDG-aligned sustainable transportation goal. Sensing involves strategic foresight; seizing depends on feedback-oriented decision-making; and transforming emphasizes digital-first strategies, each directly and positively influencing the SDG-aligned sustainable transportation goal. This study contributes to understanding how transportation SMEs respond to institutional challenges and complex regulations by applying technological advancements through dynamic capabilities in rapidly urbanizing developing economies.